The Effectiveness of Science e-LKPD Based on Discovery Learning in Improving Creative Thinking Skills of Junior High School Students - Emiliana, Dina; Mahardika, I Ketut (Peneliti.net, 2026)
This study aimed to examine the effectiveness of an electronic student worksheet (e-LKPD) based on Discovery Learning on the topics of temperature, heat, and thermal expansion in improving junior high school students’ creative thinking skills. The study employed a research and development approach using the ADDIE model, which consists of the stages of Analyze, Design, Develop, Implement, and Evaluate. The e-LKPD was validated by three experts to determine its validity, practicality, and feasibility before implementation. The implementation was conducted with students of class VII-C at SMPN 10 Jember. Data were collected through expert validation sheets, student response questionnaires, and creative thinking skill tests administered in the form of pretests and posttests. The results showed a significant improvement in students’ creative thinking skills after the implementation of the Discovery Learning-based e-LKPD. The average pretest score increased from 52.14 to 90,04 on the posttest, with an N-Gain value of 0.79, which falls into the high category. Indicator-based analysis revealed that all creative thinking indicators improved, with the fluency indicator achieving the highest N-Gain value of 0.85. These findings indicate that the Discovery Learning-based e-LKPD is effective in enhancing students’ creative thinking skills and supporting active and meaningful science learning. Therefore, the Discovery Learning-based e-LKPD can be used as an effective alternative learning material for teaching temperature, heat, and thermal expansion at the junior high school level. e-LKPD, Disovery Learning Creative Thinking Skills.